2021
DOI: 10.1016/j.redox.2021.101911
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol alleviates LD-mitochondrial damage by promoting autophagy: Implications in Parkinson's disease

Abstract: Emerging evidence indicates that unexpected lipid droplet (LD) deposition and peroxidation can accelerate organelle stress and plays a crucial role in the pathogenesis of neurodegenerative diseases (NDDs). In our previous study, we confirmed that kaempferol (Ka), a natural flavonoid small molecule, exhibited neuroprotective effects on mice with LPS-induced Parkinson's disease (PD). In addition, previous studies have shown that autophagy plays an important role in the regulation of cellular LD deposition. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 46 publications
0
40
0
Order By: Relevance
“…In previous studies [ 10 , 11 , 12 ], kaempferol has shown neuroprotective effects in animal models of PD. In these studies, the researchers used a concentration of 5 µM or higher of kaempferol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies [ 10 , 11 , 12 ], kaempferol has shown neuroprotective effects in animal models of PD. In these studies, the researchers used a concentration of 5 µM or higher of kaempferol.…”
Section: Discussionmentioning
confidence: 99%
“…Kaempferol was also reported to increase the resistance of DA neurons to neuroinflammation [ 11 ]. In addition, kaempferol apparently prevented lipid droplet toxicity in vitro and ameliorated DA neuronal loss and behavioral deficits in a PD mouse model; these effects were found to be autophagy-dependent [ 11 , 12 ]. However, the effect of kaempferol on α-Syn-related neurotoxicity induced via the autophagy pathway has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…During the last 4 min, duration of immobility (hanging passively and motionless) was recorded with TailSuspScan (Clever Sys). The rotarod test was performed as described in our previous work [ 39 ]. In brief, mice were acclimatized to the rotarod for 2 consecutive days then were tested at 20 rpm for 300 s for other 3 consecutive days.…”
Section: Methodsmentioning
confidence: 99%
“…Growing evidence suggests that lipid accumulation and inflammation in brain astrocytes are associated with an increase in neurodegenerative diseases, aging-related disorders, and brain damage, including but not limited to AD, PD, and traumatic brain injury ( 4 , 24 26 ). Clinical evidence shows that the serum levels of lipids and inflammatory factors were highly elevated in aging patients undergoing surgery ( 27 29 ).…”
Section: Methodsmentioning
confidence: 99%